2020
DOI: 10.3390/coatings10030239
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Investigation on Physical, Rheological Thermal and Microscopic Characteristics of Water-Foamed Asphalt under Three Environmental Conditions

Abstract: Applications of water-foamed binders have received widespread attention due to its environmental and economic benefits. This study aims to evaluate the properties of water-foamed asphalt under three environmental conditions (high-temperature evaporation, low-temperature frozen and the freeze–thaw cycle). Conventional physical properties tests, dynamic shear rheometer test (DSR), differential scanning calorimetry test (DSC) and scanning electron microscope test (SEM) are employed to assess the physical, rheolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The characteristics of finegrained soils, including their (micro-)structure and strength, can be affected, significantly, by consecutive freezing and thawing, which typically degrades their durability, thus posing potential risks for the long-term performance of constructed facilities. As the literature would suggest, this is a very important encountered problem in cold regions, influencing the integrity of infrastructures and structural materials [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of finegrained soils, including their (micro-)structure and strength, can be affected, significantly, by consecutive freezing and thawing, which typically degrades their durability, thus posing potential risks for the long-term performance of constructed facilities. As the literature would suggest, this is a very important encountered problem in cold regions, influencing the integrity of infrastructures and structural materials [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al evaluated the physical, rheological, and thermal properties of foamed WMA under the environmental condition of freeze-thaw (F-T) cycles. The results showed that the thermal stability and deformation resistance at high temperature were improved after F-T cycles, and the fatigue resistance was reduced [ 11 ]. It was found in the study of Liu et al that the rheological performances of foamed asphalt in the stable state binders were similar to the unfoamed asphalt [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%